Design and Optimization of MicroSolar Grid for Off-Grid Rural Communities - Alam, Khorshed; Mostakim, MD Ali; Khan, Md Shaiful Islam (International Journal of Scientific Research and Management (IJSRM), 2017)
This article provides an in-depth exploration of the design and optimization of micro solar grids for off-grid rural communities, focusing on their role as a sustainable energy solution. The global energy crisis, particularly in rural regions with limited access to the centralized grid, necessitates the exploration of decentralized energy systems. Micro solar grids, powered by solar energy, present an ideal solution, offering communities the ability to produce and consume their own electricity while reducing dependency on external power sources. This paper discusses the importance of micro solar grids as a renewable and reliable energy source that can significantly enhance the quality of life in rural communities, addressing issues such as energy access, poverty alleviation, and rural development.The article delves into the technical aspects of designing a micro solar grid, including energy demand calculations based on the community’s needs, solar panel sizing, and the integration of energy storage solutions. The optimization of system performance is discussed, covering both technical and economic strategies to maximize energy output, improve system efficiency, and reduce costs. Key optimization techniques such as panel placement, battery storage management, and energy distribution are emphasized to ensure reliable power supply, even during cloudy days or at night.